A case report of Sjögren's syndrome associated with protein-losing gastroenteropathy successfully treated with methylprednisolone. Issue 2 (October 2020) - Li, Xiaoming; Lin, Fan; Wu, Ziyu; Chen, Yan; Zhu, Pengli
Protein-losing gastroenteropathy (PLGE) is a rare manifestation of primary Sjögren's syndrome that is most commonly reported in Japan. Herein, the case of a 71-year-old Chinese male patient, diagnosed with PLGE and Sjögren's syndrome, is reported. The patient presented with peripheral oedema, and PLGE was diagnosed based on the result of technetium-99m ( 99m Tc)-labelled albumin scintigraphy. In addition to a positive Schirmer's test, the patient had atrophy of the salivary gland with lymphocyte infiltration, impaired parotid-gland secretory and excretory function, and an increased level of anti-SSA antibodies, fulfilling the criteria for Sjögren's syndrome. He was successfully treated with methylprednisolone. Follow-up 99m Tc-labelled albumin scintigraphy results correlated well with clinical improvement and increased serum albumin levels. The present case study highlights the necessity of considering a diagnosis of protein loss enteropathy associated with primary Sjögren's syndrome when patients have unexplained hypoproteinaemia.